Comparing Carotid Artery Velocities with Current ASCVD Risk Stratification: A Novel Approach to Simpler Risk Assessment - Yueh-Chien Lu; Po-Ju Chen; Sheng-Nan Lu; Fu-Wen Liang; Hung-Yi Chuang (Journal of Epidemiology and Global Health, 2024)
Abstract Purpose To explore the potential of a novel approach to simplify risk assessment by comparing carotid artery velocities with current atherosclerotic cardiovascular disease (ASCVD) risk stratification method using nonlinear measurements. Methods In this prospective study conducted at a medical center in southern Taiwan from January 1, 2020, to December 31, 2021, 1636 participants aged 40–75 years without prior ASCVD events were enrolled. Carotid flow velocity was obtained through duplex ultrasonography. ASCVD risk was categorized into two groups according to the 2022 USPSTF guidelines for primary prevention. We analyzed associations between flow indices and ASCVD risk using logistic regression and generalized additive models (GAMs). Results The end diastolic velocity (EDV) of common carotid artery (CCA) and the peak systolic velocity (PSV) of internal carotid artery (ICA) were inversely and nonlinearly associated with cardiovascular event risk. Multivariate logistic regression analysis with ROC curves revealed that the optimal speed for the EDV of CCA was approximately 23.75 cm/s, and the optimal PSV and EDV of ICA were approximately 81.75 cm/s and 26.75 cm/s, respectively. The GAMs showed U-shaped relationships between elevated ASCVD risk and blood flow velocity in the carotid arteries, with inflection points of approximately 82 cm/s in the PSV of ICA and near 25 cm/s in the EDV of CCA. Both methods revealed similar results. Conclusions The EDVs and PSVs of the CCA and ICA are associated with the development of cardiovascular events. Optimal velocity ranges were identified; however, further hemodynamic investigations are warranted.